EFFECT OF SEED SOURCE AND SEED SIZE ON THE EARLY GROWTH OF ANACARDIUM OCCIDENTALE SEEDLINGS - Yisau, J. A.; Emilimor, P. N; Odeyale, O. C.; Majolagbe, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Seed size and seed origin forms a very important element in the quality of seedlings produced in the nursery. This study investigated the effects of seed size and seed source on early growth of Anacardium occidentale seedlings. Seeds collected from mother tree at three sources (Somorin, Funaab and Camp locations) were sorted into Large, Medium and Small sizes. Collected and sorted seeds, raised in 54 poly pots was laid out in 3 x 3 factorial in Completely Randomized Design (CRD). Data was collected fortnightly for 12 weeks and it was subjected to Analysis of Variance (ANOVA) in SAS. Large sized seed had significantly (p<0.05) produced higher seedling height (26.39cm), number of leaves (10.82), leaf area (82.27cm2), collar diameter (5.20mm), total fresh weight (22.72g), total dry weight (6.26g), fresh shoot weight (18.22g) and dry shoot weight (5.09g). Seeds sourced from Funaab had significantly (p<0.05) higher effect on seedling height (26.87cm) and fresh root weight (4.87g). There was no significant difference (p>0.05) in the effect of source on some morphological parameters, Camp location had the highest effect on leaf area (77.39cm2) and collar diameter (5.19mm). Seeds sourced from Camp significantly (p<0.05) enhanced total dry weight (5.95g), dry shoot weight (4.81g) and absolute growth rate (0.60g/week). There was no significant difference (p>0.05) in the combined effect of seed source and seed size on A. occidentale seedling growth. To produce quality seedlings for out-planting purpose, it is important to choose large seed from a superior source.